ANALISIS IMPLEMENTASI UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL DARI PRESPEKTIF TEORI KEADILAN (Studi Kasus Di Kota Gorontalo) - Lion Hidjun; Agustina Bilondatu; Yusrianto Kadir (INTELIGENSIA MEDIA, 2023)
Implementation of Law Number 12 of 2022 concerning Acts of Sexual Violence from the Perspective of the Theory of Justice. Sexual violence is violence that occurs because of sexual issues. Sexual violence is generally committed against partners. Law enforcement is less effective and tends to be unable to thoroughly deal with crimes both in terms of quality and quantity. This research is a qualitative descriptive, empirical legal research method, with a statute approach and an analytical conceptual approach. The results of the study show that the implementation and enforcement of Law Number 12 of 2022 concerning acts of sexual violence in the city of Gorontalo have been carried out by law enforcement agencies following the provisions of the law accompanied by fines, then court decisions are determined by courts against perpetrators of crimes of sexual violence carried out following the demands and charges of the Prosecutor. The severity of the sentence depends on the motive, behavior of the witness, and the incident of the sexual crime. In conclusion, the implementation of law enforcement against crimes of sexual violence in the city of Gorontalo has been carried out by police agencies, prosecutors, and courts, enforcement of Law Number 12 of 2022 is carried out through Rechterlijk Pardon or pardons by judges in the form of decisions